The role of market structure and timing in determining VAT pass-through - Bellon, Matthieu,Copestake, Alexander (International Monetary Fund, 2021)
We examine the role of market characteristics and timing in explaining observed heterogeneity in VAT pass-through. We first extend existing theory to characterize the roles of imperfect competition and product differentiation, then investigate these relationships empirically using a panel of 14 Eurozone countries between 1999 and 2013. We find important roles for product market regulation and product quality, and little impact of advance announcement of reforms. Our findings have important implications for policy-makers considering VAT rate adjustments, by illuminating which of the consumers or the producers would experience the brunt of a reform across different settings
10.5089/9781513571546.001
Keywords: Graue Literatur; Price effect; Pass through; Product Differentiation; Pass Through; Price Effect; Value Added Tax; Value added tax; Competition; Taxation; Finance: General; Foreign Exchange; Informal Economy; Underground Econom; Taxation and Subsidies: Incidence; Business Taxes and Subsidies; Information and Product Quality; Standardization and Compatibility; General Financial Markets: General (includes Measurement and Data); Macroeconomics: Consumption; Saving; Wealth; Price Level; Inflation; Deflation; Economic & financial crises & disasters; Economics of specific sectors; Public finance & taxation; Finance; Financial crises; Economic sectors; Macroeconomics; Taxes; Economics: General; Financial markets; Consumption; National accounts; Commodity markets; Consumer prices; Currency crises; Informal sector; Economics; Spendings tax; International Economics; Consumption; Economics; Commodity exchanges; Prices